Risk of suffering from eating disorders students in the 1st and 2nd semester of the Medicine degree - Bareiro Recalde, Alisson Anahí; Imas Sotto, María Paz; Benítez Desvars1, Alicia Viviana; Aveiro Róbalo, Telmo Raul (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Background: eating Disorders are complex psychiatric illnesses caused by various factors, mainly during adolescence and youth. The symptomatology involves excessive concern about food, weight, and/or body image and unhealthy habits to control or reduce body weight.Methods: a cross-sectional descriptive observational study was conducted using the SCOFF and EAT-26 instruments to assess eating behavior in first and second- semester university students at a private university in Asunción, Paraguay. The questionnaire, consisting of closed-ended multiple-choice questions, was processed using Microsoft Office's Excel, enabling a detailed analysis of the sample.Results: the sample of 83 students, predominantly composed of women (74,7 %) aged between 18 and 24, showed a 41 % risk of eating disorders according to the SCOFF scale and 20 % according to the EAT-26 scale. Notably, there is a significant prevalence of women at higher risk of eating disorders compared to men. The results underscore the severity of these disorders and highlight specific risk factors in university students, such as academic stress and social pressure to maintain a slim body.Conclusion: findings from this cross-sectional study suggest a moderate prevalence of eating disorder risk in first and second-semester medical students, particularly among women. The EAT-26 survey, encompassing more items and response options, identified a 20 % risk, while the briefer and dichotomous SCOFF questionnaire reported 41 % risk prevalence. However, due to the cross-sectional design and the nature of the instruments, these findings should be interpreted cautiously. Longitudinal studies with comprehensive diagnostic assessments are needed to draw more robust conclusions about the true prevalence and incidence of eating disorders in this population.